2022
DOI: 10.1155/2022/7141837
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Household Tourism Consumption Based on Multilevel Structural Equation Model

Abstract: With the development of the social economy and the improvement of people’s living standards, tourism has become one of the important lifestyles of families. Family tourism is a new trend that will have no small impact on further developing tourism and boosting domestic demand. With tourism activities booming today, family tourism consumption is an area worthy of study. This study examines household tourism consumption using a hierarchical structural equation model to explore the factors influencing the latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Some scholars emphasize that family age structure (Bernini & Cracolici, 2015), retirement (Deng et al, 2023), and economic uncertainty (Nguyen et al, 2022) have a significant effect on TCE consumption. Based on the absolute income and persistent income hypotheses (P. Zhang & Cao, 2022), others assert that increases in current and expected incomes, as well as expected and unexpected increases in asset prices (Lee & Kim, 2021), result in expanded household consumption of travel and culture. In contrast, based on the precautionary savings theory, other scholars have found that households increase precautionary savings to manage uncertainties such as health (Gao et al, 2021) and employment (Nilashi et al, 2019), resulting in a decline in TCE consumption.…”
Section: Factors Influencing Tce Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars emphasize that family age structure (Bernini & Cracolici, 2015), retirement (Deng et al, 2023), and economic uncertainty (Nguyen et al, 2022) have a significant effect on TCE consumption. Based on the absolute income and persistent income hypotheses (P. Zhang & Cao, 2022), others assert that increases in current and expected incomes, as well as expected and unexpected increases in asset prices (Lee & Kim, 2021), result in expanded household consumption of travel and culture. In contrast, based on the precautionary savings theory, other scholars have found that households increase precautionary savings to manage uncertainties such as health (Gao et al, 2021) and employment (Nilashi et al, 2019), resulting in a decline in TCE consumption.…”
Section: Factors Influencing Tce Consumptionmentioning
confidence: 99%
“…Some scholars emphasize that family age structure (Bernini & Cracolici, 2015), retirement (Deng et al, 2023), and economic uncertainty (Nguyen et al, 2022) have a significant effect on TCE consumption. Based on the absolute income and persistent income hypotheses (P. Zhang & Cao, 2022), others assert that increases in current and expected incomes, as well as expected and unexpected increases in asset prices (Lee & Kim, 2021), result in expanded household consumption of travel and culture.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Family tourism -Academia started talking about family tourism in 1978 (Li et al, 2020). Its socio-economic impact and its continuously rising importance (Zhang & Cao, 2022) have lately led the academic world to pay more attention to families' tourism behavior (Wu et al, 2019), with a sharp but subdued rise of published studies registered in the last decade (Li et al, 2020). Family tourism manuscripts explain that the relationship between parents and children is what drives humanity and society (Schänzel & Yeoman, 2014) and, in this context, family trips have become a tool as well as a seed for enhancing the health of the traveling members (Zabriskie & McCormick, 2001), increasing children's cognitive skills (Miyakawa & Oguchi, 2022) and proliferating family happiness (Townsend et al, 2017;Schänzel & Yeoman, 2015).…”
Section: Area Of Studymentioning
confidence: 99%
“…Most of the families are planning to spend their stay at a hotel and, even though the majority of the sample population wishes to have a swimming pool in the lodging, the security at the aquatic amenities that the establishments offer are customers' biggest fear. Since family tourism represents 30 percent of the worldwide leisure travel market (Cicero & Osti, 2018) and the economic contribution of this segment to the hospitality industry is growing steeply (Zhang & Cao, 2022), data suggest hotel managers need to pay particular attention to the management of their aquatic services. Nevertheless, the researcher adds that hospitality brands should not underestimate the marketing and promotion of the aforementioned services since parents are increasing their technological use for finding the right accommodations (Agarwal et al, 2010) and advertising qualitative services plays a key role for gaining competitive advantage and achieving customer retention (Esparon et al, 2013).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The influence of e-commerce on the competitiveness of the tourism industry based on an optimized neural network model for the analysis and forecasting of tourism data was studied in [6]. To improve the model, it is planned to conduct an analysis of household impact on travel using deep learning.…”
Section: Research Of Existing Solutions To the Problemmentioning
confidence: 99%